The Plight of Children With Disabilities In Selected Areas In Bohol Province: A Proposed Integrated Rehabilitation Program - Casabal, Gloria T.; de Castro, Jeimylo C. (JPAIR Multidisciplinary Research, 2008)
The essence of childhood is growing into a well-functioning adult, but children with disabilities often face challenges that hinder this process, leading to limitations as adults. In the Philippines, approximately 6.5 million individuals live with disabilities, with 75% residing in rural or semi-urban areas where rehabilitation services are scarce or unavailable (NCSO, 2000). This issue is particularly pronounced in Bohol Province, where access to information about children with disabilities (CWD) is limited due to a lack of comprehensive data. In response, the University of Bohol College of Allied Medical Sciences (UBCAMS) conducted a study to assess the status of CWD and their families in Tagbilaran City and three municipalities. The study aimed to evaluate the extent of disabilities among children and propose an Integrated Rehabilitation Program. By doing so, it seeks to raise awareness among civil society, local government units, and relevant agencies to address the needs of CWD and provide adequate support. This initiative is crucial for ensuring that children with disabilities receive the necessary care and resources for their development. Ultimately, the study will enable UBCAMS to expand its community-based rehabilitation services, promoting inclusive development and improving access to rehabilitation services in Bohol. This coordinated effort is essential for enhancing the quality of life for CWD and their families, aligning with broader societal goals of fostering well-being and equality.